(untitled) (ESMAT Magazine, 2019)
This present work aims to bring out the reader to an analysis regarding the State’s Civil Liability in face of omissive acts regarding the public security mentioned on article 144 of the Federal Constitution. For that purpose, decisions of the Superior Courts will be emphasized, even though jurisprudence is still not homogeneous on the matter; as for the the prevalent doctrine defends that, regarding omission, liability depends on intention or fault (subjective liability), whereas the minority claims State’s liability to be independent of the demonstration of intention or fault (objective liability). From that standpoint, the object of study will be analyzed to check if the State really is responsible for its omission in providing security within public means of transportation or if only the company that explores transportation shall be responsible for crimes perpetrated within buses. The reflections of this research will be directed to a possible solution of the problem of State’s Civil Liability since public security is a collective fundamental right, and in which situations the State will be exempt of such liability.